EKSISTENSI ‘URF SEBAGAI METODE PENETAPAN HUKUM DAN APLIKASINYA PADA TRANSAKSI EKONOMI ISLAM - Haqiqotus Sa’adah (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2022)
The current condition triggers the scholars to make a rule of fiqh that can be used as a guide in making laws that have not been clearly stated in the Qur'an or Hadits. Along with the times, it is certain that the development of problems faced by society will also experience development as well as in the economic field. There are customs or traditions/customs commonly called 'urf in ushul fiqh who are widely popular in the midst of their lives. These habits can be taken into consideration when determining Islamic law in growing economic transactions, especially related to issues for which there is no legal certainty in the Qur'an and Hadits. In this study using qualitative research methods, the data sources used were fiqh and ushul fiqh rules books and articles in journals related to the theme. Data collection techniques are carried out by literature review. The results of this study are that there are two types of gharar, namely heavy gharar and light gharar. Heavy gharar is gharar that can be avoided and causes disputes between the parties to the contract. Gharar this type varies, depending on the place and location, therefore the standard of gharar is returned to 'urf (custom/tradition).